Strengthening reproductive health among female workers through the Gerakan Pekerja Perempuan Sehat Produktif program: Application of the continuous health examination network model in Indonesia - Chendra P. Putra; Afrizal Afrizal; Hardisman Hardisman; Mohamad Reza (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
The expansion of women in employment warrants more focus on reproductive health and occupational well-being. In Indonesia, the Gerakan Pekerja Perempuan Sehat Produktif (GP2SP) program has been developed to promote the health of female workers. However, the implementation of the program is still limited due to the absence of an integrated operational structure. This research is intended to create a Continuous Health Examination Network (CHEN) model in an effort to improve women’s reproductive health by revitalising the GP2SP program. While traditional workplace interventions focus on episodic services, the CHEN model incorporates ongoing monitoring, engagement with many stakeholders and promotive, preventive, curative and rehabilitative approaches. The model is useful for low- and middle-income nations, especially African settings, where workplace reproductive health services are generally fragmented. This study used a research and development design based on the ADDIE model. The investigation was cross-sectional and included 104 married female workers from two companies in Riau Province, Indonesia. Data were acquired through structured questionnaires and analyzed using descriptive statistics and chi-square testing. Model development consisted of needs assessment, model drafting, and expert validation through a two-round Delphi technique. Workers' attitudes were substantially related to program knowledge (p = 0.027). The CHEN model proved viable and may be useful for enhancing women’s reproductive health and productivity in office settings.